Analysis Of Saponin Content in Ruruhi Plant (Syzygium polycephalum Merr) in Kendari City, Southeast Sulawesi - Ode Nanang Trisna Dewi, Wa; Dewi, Fitria; Ardiansyah, Ardiansyah; Aswad, Aswad; Mantasia, St. (CV. Inara, 2023)
The Ruruhi plant (Syzygium polycephalum Merr.) is a local, unique and flowering plant belonging to the Myrtaceae tribe, the guava group, which disperses by seeds. The purpose of this study was to determine the saponin content in leaf of Ruruhi plant (Syzygium polycephalum Merr.) in Kendari City, Southeast Sulawesi Province. The analysis method uses UV-Vis Spectrophotometry. The results showed that the mature leaf of the Ruruhi plant contained 0,825 mg/10 ml of saponins and 0,566 mg/10 ml of young leaf. Thus there was a difference between the saponin content in young leaf and mature leaf, respectively 0,566 mg/10 ml and 0,825 mg/10 ml.